Evaluation of a nutritional supplement for the alleviation of pain associated with feline degenerative joint disease: a prospective, randomized, stratified, double-blind, placebo-controlled clinical trial. Issue 10 (October 2022) - Cunningham, Rachael; Gruen, Margaret E; Thomson, Andrea; Lascelles, B Duncan X
Objectives: The purpose of this study was to evaluate the pain-alleviating and activity-enhancing effects of glucosamine/chondroitin sulfate (Dasuquin) in cats that had degenerative joint disease (DJD) and owner-noted mobility/activity impairment. We hypothesized that the nutritional supplement would produce pain-relieving and activity-enhancing effects in cats with painful DJD. Methods: In this prospective, randomized, stratified, double-blind, placebo-controlled clinical trial, 59 cats with DJD pain were assigned to receive a placebo (n = 30) or supplement (n = 29) for 6 weeks after 2 weeks of placebo. Outcome measures (at-home accelerometry and client-specific outcome measures [feline (CSOMf); Feline Musculoskeletal Pain Index (FMPI); quality of life (QoL)]; and veterinarian examination) were collected at days 14, 28, 42 and 56. Results: Twenty-seven cats in the treatment group and 30 in the placebo group completed the trial. Within the first 2 weeks (placebo administration to all cats), 78% of all cats had an improvement in CSOMf scores. Both groups showed significant improvement at most time points in CSOMf, FMPI, QoL and pain scores, with the placebo group showing greater improvement than the supplement group (significant for CSOMf [ P  = 0.01]). Overall, no differences in activity were seen between the groups. Cumulative distribution function analysis indicated that for most levels of activity, the placebo-treated cats were more active; however, the least active cats were more active on the supplement ( P  = 0.013). Conclusions and relevance: This study showed a strong placebo effect. The glucosamine/chondroitin sulfate supplement did not show pain-relieving effects when compared with placebo.